The value-target factors of future journalists’ life- creation - Karpenko, Zinoviia; Karpenko, Yevhen (Journal of Education Culture and Society, 2021)
Aim. The study purpose is to explain the value-targeted predictors of future journalists’ life-creation as an indicator of their readiness for professional growth and fulfilment of their humanitarian mission. Methods. The study used the methods of theoretical analysis, synthesis and modelling of the process of personality realization. The empirical study on the value-target factors of future journalists’ life-creation consisted of two stages: 1) the selection of relevant psychological examining techniques in order to explain the value-target factors as a complex independent variable, on the one hand, and the corresponding features of the life implementation process as characteristics (partial and generalized) of a dependent variable, on the other hand (a total of 12 psychodiagnostic techniques were used); 2) the correlation and factor analyses of the obtained empirical data.Results. The performed factor analysis revealed several factors related to particular modes of life implementation, an individual’s certain subjective position in this mode or on the way to it, psychological mechanisms and predictors of becoming an Insider, Expert or Author in personal life, some of their important attributes that generally confirm the triangulation model of an individual’s life implementation. The first one, “An Author – a life-creating agent in the integrative mode of life implementation”, is the most informative and the most loaded by the following indicators: life meaningfulness and purpose in life, psychological well-being, existential fullness with life meaning, self-control and self-acceptance, activity, locus of control-life, etc.  Conclusions. The article presents the verification of the triangulation psychological-hermeneutic model of a life-implementation process, which is formed by orthogonal vectors: one of them is intuitive-sensory comprehension and designing and the second is discursive-logical goal-setting and achievement of life aspirations by an individual. The performed factor analysis of the value-target factors of future journalists’ life-creation revealed the relevant predictors of life implementation. They concerned such concepts as an individual’s life position (a Reader and an Author, an Observer and an Insider, an Epigone and an Expert); the trajectory of their life, for example, from an Insider to an Author, or from an Epigone to en Expert; and psychological mechanisms of life implementation (reflection, intuition, anticipation, empathy, facilitation, etc.) in certain life-implementation modes (internal, external and integrative).